Anaerobic Digestion of the Halophyte Salicornia ramosissima in Co-Digestion with Swine Manure in Lab-Scale Batch and Continuous Reactor Tests - Aadila Cayenne; Hinrich Uellendahl (Energies, 2025)
This laboratory study investigated the anaerobic co-digestion process of the halophyte S. ramosissima (Sram) together with swine manure (SM) in different mixing ratios in batch and continuous reactor experiments. In the batch experiments, a methane yield of 214 mLCH4·gVS−1 was obtained for Sram in mono-digestion. In co-digestion with SM, the methane yields were slightly higher than calculated from the yields of each substrate in mono-digestion. Also, the kinetic rate constant in the co-digestion with swine manure increased from 0.219 d−1 for mono-digested S. ramosissima to 0.318 d−1 in the co-digestion of 50:50 Sram:SM (based on VS). Two continuous 5 L lab-scale CSTR reactors were operated: one as a control (100% SM) and the other as a co-digestion reactor with an increasing VS share of Sram (15, 25, and 35%) in the feed. Both reactors were operated at an organic loading rate (OLR) of 2.5 gVS.L−1·d−1 and a hydraulic retention time (HRT) of 20 days. In the continuous process, the highest methane yield of 276 mLCH4·gVS−1 was achieved at a co-digestion VS ratio of Sram:SM 25:75, corresponding to a methane yield from the added S. ramosissima of 277 mLCH4·gVS−1. This showed successful operation of the continuous co-digestion process of S. ramosissima and swine manure, with higher methane yields of S. ramosissima than in the mono-digestion batch tests.